Enhanced visible-light-photoconversion efficiency of TiO2 nanotubes decorated by pulsed laser deposited CoNi nanoparticles. (5th November 2019) - Favet, Thomas; Keller, Valérie; Cottineau, Thomas; El Khakani, My Ali
Abstract: The pulsed laser deposition (PLD) technique has been used to decorate TiO2 nanotubes (NTs) with cobalt-nickel (CoNi) nanoparticles (NPs). The TiO2 NTs were produced beforehand through the controlled anodic oxidation of titanium substrates. The effect of the nature of the PLD background gas (Vacuum, O2 and He) on the microstructure, composition and chemical bondings of the CoNi-NPs deposited onto the TiO2 -NTs has been investigated. We found that the PLD CoNi-NPs have a core/shell (oxide/metal) structure when deposited under vacuum, while they are fully oxidized when deposited under O2 . On the other hand, by varying the CoNi-NPs loading of the TiO2 -NTs (through the increase of the number of laser ablation pulses (NLP )), we have systematically studied their photocatalytic effect by means of cyclic-voltammetry (CV) measurements under both AM1.5 simulated solar light and filtered visible light. We show that depositing CoNi-NPs on the substrate under vacuum and He increases the photo-electrochemical conversion effectiveness (PCE) by 600% (at NLP = 10, 000) in the visible light domain, while their overall PCE degrades with NLP under solar illumination. In contrast, the fully oxidized CoNi-NPs (deposited under O2 ) are found to be the most effective catalyst under sunlight with an overall increase of more than 50% of the PCE at the optimum loading around NLP 1000. Such catalytic enhancement is believed to result from both an enhanced light absorption by CoO (of which bandgap is of 2.4 eV) and the formation of a heterojunction between NiO/CoO nanoparticles and TiO2 nanotubes. Graphical abstract: Image 1 Highlights: Pulsed laser deposition was used to decorate TiO2 nanotubes with CoNi nanoparticles. Photo-electrochemical activity is enhanced ( 50%) by CoNi nanoparticles under sunlight. Chemical composition and loading of CoNi nanoparticles can be easily adjusted. Optimum catalyst loading was identified.